2021
DOI: 10.1080/08039488.2021.1894231
|View full text |Cite
|
Sign up to set email alerts
|

Depression and loneliness may have a direct connection without mediating factors

Abstract: Purpose of the article: There is growing interest in loneliness and its various adverse effects on mental and physical health. While depression is one of the adverse health effects associated with loneliness, there have been some limitations in previous studies: 1) Research has mostly been carried out either in depressed patient samples or in general population samples with depressive symptoms as an outcome, 2) the follow-up times have been rather short, and 3) the mechanisms through which loneliness associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 30 publications
0
5
1
Order By: Relevance
“…The hypotheses formulated were all confirmed. The analyses conducted showed that, in line with the first hypothesis, well-being is negatively correlated with loneliness, social isolation, and perceived age discrimination in the context of the COVID-19 pandemic [ 11 , 66 , 67 ], while it is positively correlated with positive affect, confidence in the future, and physical health [ 68 , 69 ]. With regard to the second hypothesis, the model tested presents good fit indices and the relationships were all confirmed.…”
Section: Discussionmentioning
confidence: 70%
“…The hypotheses formulated were all confirmed. The analyses conducted showed that, in line with the first hypothesis, well-being is negatively correlated with loneliness, social isolation, and perceived age discrimination in the context of the COVID-19 pandemic [ 11 , 66 , 67 ], while it is positively correlated with positive affect, confidence in the future, and physical health [ 68 , 69 ]. With regard to the second hypothesis, the model tested presents good fit indices and the relationships were all confirmed.…”
Section: Discussionmentioning
confidence: 70%
“…Students who live alone or have a bad relationship with people around report severe depression ( Shao et al, 2020 ). Furthermore, studies show that loneliness stably predicts depression and can be an antecedent risk factor for depression ( Qualter et al, 2010 ; Vanhalst et al, 2012 ; Matthews et al, 2016 ; Kraav et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Further analysis of data in this study showed that 21.24% of lonely and more anxious elderly were within the low socioeconomic groups while 5.12% were in the high socioeconomic groups. Other studies have shown that living alone was strongly associated with depressive symptoms and depression [ 57 , 63 65 ] and anxiety [ 66 ] in elderly. In this regard, Berkman believes that social support creates a sense of intimacy through emotional patronage.…”
Section: Discussionmentioning
confidence: 99%